2013
DOI: 10.1371/journal.pone.0075322
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Decreases Bone Loss, Inflammation and Oxidative Stress in Experimental Periodontitis

Abstract: The aim of this study is to determine the effects of Atorvastatin treatment, an inhibitor of 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase, in periodontal disease. Male Wistar albino rats were randomly divided into five groups of ten rats each: (1) non-ligated treatment (NL), (2) ligature only (L), (3) ligature plus 1 mg/kg Atorvastatin daily for 10 days, (4) ligature plus 5 mg/kg Atorvastatin daily for 10 days, and (5) ligature plus 10 mg/kg Atorvastatin daily for 10 days. Following the treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 26 publications
3
21
1
1
Order By: Relevance
“…Some previous studies have reported significant increases, significant decreases and non-significant changes in SOD and/or GSH-Px levels in patients with periodontitis relative to healthy subjects (14)(15)(16)(17)(18). In the present study, the levels of SOD and GSH-Px did not differ significantly among any of the groups.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…Some previous studies have reported significant increases, significant decreases and non-significant changes in SOD and/or GSH-Px levels in patients with periodontitis relative to healthy subjects (14)(15)(16)(17)(18). In the present study, the levels of SOD and GSH-Px did not differ significantly among any of the groups.…”
Section: Discussioncontrasting
confidence: 58%
“…The antioxidant function of GSH plays a significant role in its direct scavenging of ROS (50). It has been reported that serum GSH levels are increased in experimental periodontitis (14). Schupp et al (51) reported that GSH was increased in human promyelocytic cells incubated with/without rosuvastatin, inducing the formation of ROS, and that this effect was independent of HMG-CoAR inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies with antihypertensive drugs have shown that they have an anti-inflammatory activity in periodontal disease with reduced bone loss [2][5]. Our group have study the angiotensin II receptor blocker (ARB).…”
Section: Introductionmentioning
confidence: 99%